Cotrimoxazole Prophylaxis Specifically Selects for Cotrimoxazole Resistance in Streptococcus mutans and Streptococcus sobrinus with Varied Polymorphisms in the Target Genes folA and folP - Buwembo William; Charles Mugisha Rwenyonyi; Göte Swedberg; Fred Kironde (International Journal of Microbiology)
The selection of antibiotic resistance by cotrimoxazole prophylaxis was evaluated, and we characterized the mechanism of cotrimoxazole resistance in Streptococcus mutans and Streptococcus sobrinus. In vitro susceptibility to six antibiotics was evaluated on 64 mutans streptococci group (MSG) isolates from a cotrimoxazole prophylaxis group and compared to 84 MSG isolates from a nonprophylaxis group. The folA and folP genes were sequenced and compared with reference sequences at NCBI. Only resistance to cotrimoxazole was significantly higher in the prophylaxis group (54.7% versus 15.5%, OR=6.59, 95% CI: 2.89–15.3, P<0.05). Resistance to amoxicillin, ceftriaxone, chloramphenicol, erythromycin, and tetracycline was 1.4%, 25.5%, 6.2%, 6.5%, and 29.6% of the isolates, respectively. Considerable polymorphisms were found in the folP gene in S. mutans, but this could not be linked to sulfonamide drug resistance. No variation was seen in folP or folA genes of S. sobrinus. Genetic transfer of folate pathway genes seems unlikely in these isolates.